Health and relationship quality of sexual minorities in Europe - Francesco Berlingieri; Matija Kovacic (Journal of Population Economics, 2025)
A growing body of literature investigates inequalities between sexual minorities and their heterosexual peers. This paper deals with disparities in health, health-related behaviours, and relationship quality among LGB+ individuals. We use a novel data set that allows for a wide cross-national analysis (27 EU member states) of disparities between sexual minorities and the rest of the population, as well as differences in reporting sexual orientation. We consider a rich set of social stressors, individual-specific behavioural factors, and health outcomes, as well as novel para-data (i.e., individuals' response times) that are not available in other large surveys. The results indicate that sexual minorities are more exposed to stigma-related social stressors (both in childhood and adulthood), report worse physical and mental health conditions, feel more lonely, and are more likely to engage in coping strategies aimed at reducing or adapting to stressful conditions. Some of these findings significantly differ across gay, lesbian, and bisexual individuals and with respect to household income, the country's enforcement of sexual minorities' rights, and relationship status.
Keywords: J12; J16; K38; 330; LGB+; Social stressors; Behavioural risks; Health; Loneliness